Validitas Media Pop-up Book Tiga Dimensi pada Materi Tata Surya untuk Siswa Kelas IV Sekolah Dasar - Alfiyatul Hidayah; Iis Daniati Hidayah; Ina Agustin (Tunas Nusantara, 2026)
The low learning outcomes of grade IV students at SD Negeri Gedongombo 1 on the solar system topic are presumed to be related to the limited availability of concrete and interactive learning media. This condition underscores the need for innovative instructional materials capable of bridging the gap between abstract astronomical concepts and the cognitive capacity of grade IV students, who remain at the concrete-operational stage. This study aims to examine the validity of three-dimensional pop-up book media on the solar system topic as an IPAS (natural and social science) learning medium for grade IV. The research employed a Research and Development (R&D) method at the product-validation stage, using descriptive quantitative analysis based on assessments from three independent validators (a language expert, a content expert, and a media expert) using a 1-5 Likert-scale instrument. The language expert validation yielded 100% (Very Valid), the content expert 94% (Very Valid), and the media expert 96% (Very Valid), with an overall average of 96.7%. All three validators confirmed the media is feasible for use without substantial revision. Because this study is limited to the expert-validation stage, claims regarding actual improvement of student learning outcomes require further testing through practicality and effectiveness trials involving students.